Lower Urinary Tract Symptoms, Serum PSA, Digital Rectal Examination and Prostate Volume in Patients Presenting to Urology Department: A Cross-Sectional Study - Raya, Akash; Bhatta, Pahupati; Sah, Sanjay; Aryal, Vibina (Journal of Institute of Medicine Nepal, 2022)
Introduction: Lower urinary tract symptoms (LUTS) are common presentation in the urology department in males after 50 years. Enlarged prostate can be evaluated by digital rectal examination (DRE) and ultrasound. Serum prostate-specific antigen (PSA) has been suggested as a reliable tool to estimate prostate volume (PV) and to predict the diagnosis of prostate cancer. The aim of this study is to correlate prostate-specific antigen with clinical data like age and international prostate severity score (IPSS), DRE finding and PV among subjects with LUTS. Methods: Total of 175 cases were included in the cross-sectional study who presented with LUTS in the Urology Department. DRE was done and noted. Then the cases were advised for ultrasonography (USG) and serum PSA level was sent for investigation. According to the history given by the cases IPSS was done using the IPSS scoring questions. The result was obtained by grouping the cases according to the level of serum PSA Results: The mean age of the total 191 cases was 72.23±10.46 years and mean PSA level in our study population was 9.08±23.69 ng/ml. Grade III PV was seen among 47.1% of the study population. IPSS scoring between 8-19 was seen among 68.1% study population. Correlation between serum PSA and age group (p=0.007) was significant. High significance (p<0.001) was seen in correlation between serum PSA and DRE finding, IPSS and PV. Conclusion: Our study showed that serum PSA level plays an important role in the evaluation of prostate enlargement. The level of serum PSA along with presenting symptoms and clinical findings can help us to plan our mode of treatment accordingly.